The influence of outdoor-based discovery learning model on critical thinking skill in ecosystem material - Tri Agustini; Nike Anggraini; Khoiron Nazip (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The strategy of outdoor learning can be combined with various models and methods. The discovery learning model is one approach that can be integrated with outdoor learning and can be utilized in biology education. The purpose of this study is to ascertain how the outdoor-based Discovery Learning methodology affects Class X pupils' ability to think critically about Ecosystem content.This research was conducted from February 2024 to March 2024, in the academic year 2023–2024, during the second semester. Pre-experimental study using a one-group pre-test post-test design was the methodology employed. The population of this study consisted of 30 students from a private high school in Palembang. Tests assessing critical thinking abilities and learning outcomes, each with fifteen multiple-choice questions, were the tools utilized. Critical thinking skills and learning outcomes data were analyzed using the paired sample t-test in SPSS Version 22.0. The use of the outdoor-based Discovery Learning paradigm enhanced both learning outcomes and critical thinking abilities, as evidenced by the moderately categorized N-gain values for learning outcomes (0.66) and critical thinking skills (0.69). The hypothesis test results for critical thinking skills and learning outcomes showed a sig. (2-tailed) value of 0.000 < 0.05, indicating that H0 was rejected and H1 was accepted. This demonstrates that the outdoor-based Discovery Learning model has an effect on the critical thinking skills and learning outcomes of Class X students at Patra Mandiri 2 High School in Palembang on ecosystem material.